HUBUNGAN PENGETAHUAN DASAR KOMPUTER DAN MOTIVASI DENGAN HASIL BELAJAR ALGORITMA PEMROGRAMAN SISWA KELAS X JURUSAN REKAYASA PERANGKAT LUNAK (RPL) (Survei Pada Sekolah Menengah Kejuruan Negeri di Kabupaten dan Kota Bekasi) - Adkha, Ibnu; Soeprijanto; Sastrawijaya, Yuliatri (Jurnal Pendidikan Teknik dan Vokasional, 2020)
This research is to find out and analyze empirically the relation of basic computer knowledge and motivation upon programming Algorithm achievement. The observed population of this research is students from state vocational schools in Bekasi. The sample was gained through simple random sampling. The result of this research is: 1) There is a significant relationship between basic computer knowledge and programming Algorithm achievement. It is proved by Sig.= 0.000 < 0.05 and tobserved = 9.783; 2) There is a significant relationship between motivation and programming Algorithm achievement. It is proved by Sig.= 0.000 < 0.05 and tobserved = 9.369; 3) There are significant relationships between basic computer knowledge and motivation altogether towards programming Algorithm achievement. It is proved by Sig.= 0.000 < 0.05 and Fobserved = 200.177. Keywords: basic computer knowledge, motivation, programming algorithm achievement.